Apixaban used for the management of heparin‐induced thrombocytopenia in a 72‐year‐old woman with lung cancer. Issue 12 (29th October 2015) - Larsen, Pia Bükmann; Jørgensen, Maja; Friis‐Hansen, Lennart; Ingeberg, Steen
Key Clinical Message: Heparin‐induced thrombocytopenia (HIT) is a serious adverse reaction to heparin treatment with a high risk of thrombosis. Heparin must be discontinued immediately and replaced with alternative anticoagulants that do not interact with HIT antibodies. In this case, a lung cancer patient, diagnosed with HIT was successfully treated with apixaban. Abstract : Heparin‐induced thrombocytopenia (HIT) is a serious adverse reaction to heparin treatment with a high risk of thrombosis. Heparin must be discontinued immediately and replaced with alternative anticoagulants that do not interact with HIT antibodies. In this case, a lung cancer patient, diagnosed with HIT was successfully treated with apixaban.